GROWTH OF Dunaliella sp. AS A FIRST STEP FOR TOXICITY TEST OF HEAVE METALS LEAD AND CADMIUM - M Iqbal Al Faridzi; Budijono Budijono; Andri Hendrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTMicroalgae have an important position as primary producers which have the first trophic level in the food chain of aquatic ecosystems. One of them is Dunaliella sp. Lead and cadmium are non-essential heavy metals that are toxic to aquatic organisms. The purpose of this study was to determine the growth of Dunaliella sp. for heavy metal toxicity tests. Observations were made for 14 days to see all growth phases of Dunaliella sp. The results showed that there were 4 growth phases of Dunaliella sp. namely the lag phase, the exponential phase, the stationary phase and the dying phase. The  microalgae Dunaliella sp. met the requirements for heavy metal toxicity test on day 4 or in the exponential phase and the minimum limit for the cell density of the test biota was (1 x106 cells/ml) according to ACCPMS -11 (1995).Keywords : Dunaliella sp., Toxicity test,  Exponential phase, Phytoplankton,       Heavy Metals